2015
DOI: 10.1080/15384101.2015.1033597
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic activity of survivin is regulated by acetylation at K129

Abstract: Survivin is a cancer-associated protein regulated by multiple factors, including acetylation at K129 within its C-terminal a-helical tail. Acetylation of survivin is being pursued as a potential prognostic marker in breast cancer. This modification at K129 may cause nuclear accumulation of survivin in interphase cells; however, whether this affects its essential role during mitosis has not been addressed. We posited whether mimicking acetylation of survivin at K129 alters its activity during mitosis. Fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…We found that OBP-801 treatment of dividing RMS cells induced γH2AX-positive aberrant metaphase morphologies, concurrent with lower levels and misalignment of survivin. Recently, Aljaberi et al reported that the activity of survivin in mitosis was regulated by cyclical acetylation and deacetylation during mitosis (33), which may explain how an HDAC inhibitor could induce mitotic arrest via survivin in a manner consistent with our results. These results indicated that OBP-801 may induce apoptosis in RMS cells via mitotic catastrophe.…”
Section: Discussionsupporting
confidence: 89%
“…We found that OBP-801 treatment of dividing RMS cells induced γH2AX-positive aberrant metaphase morphologies, concurrent with lower levels and misalignment of survivin. Recently, Aljaberi et al reported that the activity of survivin in mitosis was regulated by cyclical acetylation and deacetylation during mitosis (33), which may explain how an HDAC inhibitor could induce mitotic arrest via survivin in a manner consistent with our results. These results indicated that OBP-801 may induce apoptosis in RMS cells via mitotic catastrophe.…”
Section: Discussionsupporting
confidence: 89%
“…Survivin plays an important role in the regulation of mitosis [ 30 , 33 ]. It is expressed in a cell cycle dependent manner as reported mostly in G2-M phase [ 34 ].…”
Section: Survivinmentioning
confidence: 99%
“…Survivin is essential for targeting the CPC to the centromere during mitosis (Kelly et al, 2010;Wang et al, 2010;Yamagishi et al, 2010), and it undergoes phosphorylation and acetylation, which affect its functions (Aljaberi et al, 2015;Barrett et al, 2011Barrett et al, , 2009Colnaghi and Wheatley, 2010;O'Connor et al, 2000;Wheatley et al, 2007Wheatley et al, , 2004. It is not fully understood, however, how these modifications regulate the activity of survivin during mitosis.…”
Section: Introductionmentioning
confidence: 99%